THE ROLE OF SUBJECT TEACHER DELIBERATION IN IMPROVING THE COMPETENCY OF ISLAMIC RELIGIOUS EDUCATION TEACHERS AT SYARIF HIDAYATULLAH SENIOR HIGH SCHOOL - Muhammad Noor Fallah (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to examine the role of the Islamic Education Subject Teacher Consultative Forum (MGMP PAI) in enhancing teacher competencies at SMA Syarif Hidayatullah Cirebon. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The informants comprised five participants, including three core administrators and two active MGMP PAI members. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The results indicate that MGMP PAI plays a strategic role in improving teachers' four core competencies—pedagogical, professional, social, and personality. This enhancement is achieved through various collaborative programs such as workshops, scientific discussions, lesson plan development, and evaluation training. The success of these programs is supported by strong member commitment, government policies, and institutional backing. However, several significant obstacles persist, including time constraints, funding limitations, and technological gaps among teachers. In conclusion, MGMP PAI serves as an effective and strategic platform for the continuous professional development of senior high school PAI teachers, although it requires enhanced active participation and technological adaptation for more optimal outcomes.